Tenascin-C is Strongly Expressed in the Anterior Vaginal Walls of Women with Pelvic Organ Prolapse - Sulham, Risma N. (Indonesian Journal of Obstetrics and Gynecology, 2013)
Objectives: To compare the expression of tenascin in the anterior vaginal wall in women with pelvic organ prolapse and without pelvic organ prolapse (POP). Method: This study was a cross sectional study. The study was conducted in RS Dr. Wahidin Sudirohusodo and other network hospitals of Obstetrics and Gynecology Department of Hasanuddin University, Makassar, from 1st January 2011 to 1st April 2012. This study assessed the expression of tenascin in 35 women with pelvic organ prolapse grade III and IV and the controls were 35 women without pelvic organ prolapse. Tenascin expression was assessed by immunohistochemical examination using tenascin antibody staining (mouse monoclonal antibody Novacastratenascin C, code NCLTenasC). Sampling was done by consecutive sampling. Data processed by the chi-square. The significance level used was 0.05. Result: The result of this research shows that with exception of history of bearing baby > 4000 gr weight (p=0.572); age, parity, menopausal status, and body mass index were significantly different between the group. This indicates that the variable does not affect the calculation of research data. While parity, menopausal status and body mass index (BMI), from an analysis of risk factors for POP were associated with increased intensity of tenascin is significant in postmenopausal status, and BMI > 25 (overweight) (p